Pengembangan history audio podcast (Histodio) materi peperangan Masa Kerajaan Majapahit untuk Kelas X OTP SMK PGRI 2 Malang - Anggyyansyah Yusuf Mustaghfirin; Blasius Suprapta; Ulfatun Nafi'ah (Historiography: Journal of Indonesian History and Education, 2021)
This research is motivated by the history learning problems that the researchers got when observing the process of history learning activities in class X SMK PGRI 2 Malang on September 8, 2019. Some of the problems found were the first, many students did not pay attention to the teacher and focused on smartphones- at the time of history learning takes place. The second problem is the lack of innovation in learning media used coupled with the limited number of source books in schools, so students often have to take turns with other classes. The third problem, learning the history of the Majapahit Kingdom material in class X is experiencing obstacles. The Majapahit Kingdom material in history textbooks only discusses chronology in general. There is an opportunity to study the material for the War of the Majapahit Kingdom based on the up-to-date material that has not been widely studied. This study uses the ADDIE procedural model by Tegeh, et al with quantitative & qualitative research instruments, namely validation data from material experts and media experts as well as qualitative instruments in the form of field observations, online questionnaires and interviews. The reason for choosing the ADDIE model is because it allows researchers to evaluate at each stage of the study. The results of the material validation test yield a percentage of 76.9 percent, which means this product is valid for use with revisions. The results of the media validation test obtained a percentage of 95.5 percent with a very valid category used without revision. This study did not conduct trials in schools due to the covid 19 pandemic. Based on these results, it is known that the Histodio media product of war material during the Majapahit Kingdom can be said to be suitable for use as a learning media for history class X OTP at SMK PGRI 2 Malang, especially during the covid 19 pandemic. Suggestions for the next developer is to be able to develop similar media products with different materials. Penelitian ini dilatarbelakangi oleh permasalahan pembelajaran sejarah yang didapatkan peneliti saat melakukan pengamatan dalam proses kegiatan pembelajaran sejarah di kelas X SMK PGRI 2 Malang pada tanggal 8 September 2019. Beberapa permasalahan yang ditemukan adalah yang pertama, banyak siswa yang tidak memperhatikan guru dan fokus dengan smartphone-nya pada saat pembelajaran sejarah berlangsung. Permasalahan kedua yaitu kurang adanya inovasi media pembelajaran yang digunakan ditambah dengan jumlah buku sumber yang terbatas di sekolah, sehingga tak jarang siswa harus bergantian dengan kelas lain. Permasalahan ketiga, pembelajaran sejarah materi Kerajaan Majapahit di kelas X mengalami hambatan. Materi Kerajaan Majapahit yang ada di buku teks sejarah hanya membahas kronologi secara umum. Ada peluang untuk mengaji materi Peperangan Masa Kerajaan Majapahit berdasarkan pada keterbaruan materi yang belum banyak dikaji. Penelitian ini menggunakan model prosedural ADDIE oleh Tegeh, dkk dengan instrumen penelitian kuantitatif & kualitatif yaitu data validasi ahli materi dan ahli media serta instrumen kualitatif dalam bentuk hasil observasi lapangan, angket online dan wawancara . Alasan pemilihan model ADDIE karena memungkinkan peneliti melakukan evaluasi pada setiap tahap penelitian. Hasil uji validasi materi menghasilkan persentase sebesar 76.9 persen yang artinya produk ini valid untuk digunakan dengan revisi. Hasil uji validasi media memperoleh hasil persentase 95.5 persen dengan kategori sangat valid digunakan tanpa revisi. Penelitian ini tidak melakukan uji coba di sekolah dikarenakan adanya pandemi covid 19. Berdasarkan hasil tersebut diketahui bahwa produk media Histodio materi peperangan masa Kerajaan Majapahit dapat dikatakan layak untuk digunakan sebagai media pembelajaran sejarah kelas X OTP di SMK PGRI 2 Malang terutama pada masa pandemi covid 19. Saran bagi pengembang selanjutnya adalah dapat mengembangkan produk media serupa dengan materi yang berbeda.